PELATIHAN DIGITAL LITERACY DAN PERSONAL BRANDING BAGAI MAHASISWA EKONOMI SYARIAH - Latifah, Eny; Prazetya, Donny (Jurnal Pengabdian Masyarakat Berkarya, 2024)
The title of this Community Service is Digital Literacy and Personal Branding Training for Sharia Economics Students. The purpose of this training is to increase the understanding of students of the Sharia Economics Study Program at Tarbiyatut Tholabah Islamic Institute in personal branding and digital literacy in facing the rapid advancement of information technology to the fullest. The result of the service is that students' understanding of personal branding and digital literacy is still low, this can be seen from the pre-test given by students as service participants. The next effort is to provide comprehensive training related to personal branding and digital literacy. To find out the improvement can be seen from the post test results. There is a change in understanding where before the post test the average participant correctly answers only 10% and after the post test it becomes 75% of the questions given related to personal branding and digital literacy.